Composition of the Council of Judges: changes in regulation in Lithuania in 1994–2019 - Šinkūnas, Haroldas; Driukas, Artūras (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The article examines the changes in the legal regulation of the composition of the special institution of judges provided for in Paragraph 5 of Article 112 of the Constitution, which is enshrined in the current Law on Courts from the establishment of this institution in 1994 until the last amendments made in 2019. In carrying out the tasks assigned to it by the Constitution, the Council of Judges acts as a counterweight to the President of the Republic in questions of the formation of the judicial corps and as one of the most important institutions of judicial self-government and fulfills a very important mission to protect the independence of the judiciary and judges. The article examines the ruling of the Constitutional Court of 9 May 2006, which determined the fundamental changes in the composition of the Council of Judges, in which it was clarified that only judges may be members of this institution. The authors make suggestions that, in their opinion, would create preconditions for improving the efficiency of the Council of Judges: to establish a ban on electing the Presidents of the Supreme Court and the Supreme Administrative Court of Lithuania, to reduce the excessive influence of judges of higher courts and chairmen of courts in the self-government of courts, to set proportional quotas for the representation of judges of all courts, to elect all elected members of the Council of Judges at the General Meeting of Judges and to include not only judges in the composition of the Council of Judges.